Spanish Views of Nazi Germany, 1933–45: A Fascist Hybridization?. (October 2019) - Núñez Seixas, Xosé M.
From the early 1930s, admiration for Hitler and Nazi Germany became characteristic of Spanish fascists. They were fascinated by the image of National Socialism and its example of 'national resurgence'. During the war, the influence of Nazi Germany among Spanish fascists, traditionalists and supporters of the emerging Franco regime increased. On their return, Spanish travellers to Nazi Germany portrayed an enthusiastic image of a new society, marked by strong national pride, economic resurgence, social solidarity and material welfare. Until the end of the Second World War, several thousand Spanish Fascists and supporters of the Franco Regime visited Nazi Germany as soldiers on their way to and from the Eastern front, as civil workers or as students. A study of the experiences of such individuals may broaden our perspective on how Nazi Germany influenced foreign visitors. What image of Nazi Germany did those visitors paint in their letters, diaries and memoirs? What was left from this experience in post-1945 Spanish memories?